2011
DOI: 10.1128/jcm.00575-11
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis as a Manifestation of Parvovirus B19 Infection

Abstract: There are few reports in the literature of hepatitis as a manifestation of parvovirus B19 infection. We describe a case of parvovirus B19-associated acute hepatitis diagnosed based on a positive serologic test (IgM) and molecular detection of parvovirus B19 DNA in a liver biopsy specimen. Parvovirus B19 infection should be considered in the differential diagnosis of patients presenting with acute hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 13 publications
(14 reference statements)
2
18
0
8
Order By: Relevance
“…The pathogenesis of parvoviruses is generally associated with their predilection for actively dividing cells and different parvoviruses have different organ tropism ( 32 ). Parvovirus hepatitis in other species is rare, although parvovirus B19 can be associated with acute hepatitis in humans after transfusion of contaminated blood products ( 33 , 34 ). …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of parvoviruses is generally associated with their predilection for actively dividing cells and different parvoviruses have different organ tropism ( 32 ). Parvovirus hepatitis in other species is rare, although parvovirus B19 can be associated with acute hepatitis in humans after transfusion of contaminated blood products ( 33 , 34 ). …”
Section: Discussionmentioning
confidence: 99%
“…The virus, provisionally named parvovirus-like hybrid virus (PHV), was detected in samples from patients with chronic seronegative (non-A-E) hepatitis and diarrhea of unknown etiology. The initial finding of a novel parvovirus-/circovirus-like agent in these patients was of great interest because these viruses are known to broadly infect insects, vertebrate animals, and humans (27)(28)(29), and specific members, such as parvovirus B19 in humans and porcine circovirus type 2 (PCV2) in pigs, have been linked to hepatitis (30)(31)(32). Furthermore, a study by Xu et al recently described the discovery of a hybrid DNA virus in serum samples from Chinese patients with seronegative hepatitis, named NIH-CQV, with a sequence nearly identical to that of PHV (33).…”
mentioning
confidence: 99%
“…Although B19 infection has been implicated in pathogenesis of liver diseases and development of SLE, the effects of B19 and its viral proteins including NS1, VP1u and VP2 on hepatic injury in SLE is still obscure [6], [9][16]. In the present study, we revealed the aggravated effects of B19 NS1 protein on hepatic injury in NZB/W F1 mice by significantly enhancing the expressions of iNOS and COX-2 proteins and lymphocyte infiltration.…”
Section: Discussionmentioning
confidence: 46%
“…Indeed, various studies have postulated a connection between B19 infection and liver injury. A clinical study reported the existence of B19 DNA in a liver biopsy specimen from a patient with acute hepatitis [9]. Another studies also suggested an important role of B19 infection in acute icteric hepatitis liver injury [10] and acute fulminant hepatitis with bone marrow failure [11].…”
Section: Introductionmentioning
confidence: 99%